性别与翻译 ：以译者吴明珠及其翻译为例 = Gender and translation : using Goh Beng Choo and her translations as an example - 潘雋詠 Poon, Chern Yung (2018)
吴明珠 (1952- ) （以下简称吴氏）自80年代以来，已活跃于新加坡译坛之上，并一直担当重要的位置：她既拥有资深的译历，她的译作亦极多面向：她先于新加坡《海峡时报》双语版担当任记者，开始多种文艺翻译工作，包括文学作品、艺术评论与文化翻译等。而众所周知的是，她是新加坡重要作家英培安（新加坡文化奖得主）的“御用”译者：她既为英培安的妻子，不但一直热心支持他的创作事业，更以自己擅长的翻译，让英培安的作品在英语世界率先亮相，化译笔为实质支持，从这可看出她对新加坡文学作品的慧眼以及先驱意义。可惜的是，学界对她的研究并不多，甚至没有一篇正式的学术论文全面整理及探讨吴氏的翻译贡献。事实上，现在对于80年代新加坡译坛的研究及译者钩沉，大部分都以男性译者为主。这不单可以视为译界有云“译者被隐身” (translator’s invisibility) 的问题，更甚的是因性别意识偏颇而出现了女性译者被双重隐去，及被文化权力边缘化的情形。 有鉴于此，本论文以性别与翻译的理论框架，探讨吴明珠的翻译贡献，并着重分析吴氏如何在一个以男性为主的群体中展现自己的声音与文化身份。学者谢莉·西蒙 (Sherry Simon) 认为，翻译是女性译群发表自己声音的重要平台，研究历史上女性的译者，能还原被遗忘及忽略女性译者的精神面貌外，更重要的是呈现译界本来多元纷陈的声音。因此，本论文先集中讨论吴明珠以保育新加坡文化根的心态，分析她如何通过翻译守护艺术与文化的传承；然后重点分析吴明珠文学翻译下的英培安作品，以此表现吴明珠译者的主体性——这包括她主导选取译品、以译文质疑并反抗男性的文化权力，并在译作周边工作致力提倡女性译者的翻译地位，以身作则，改写了女性群体多年处于隐而不见的状态。 Goh Beng Choo (1952- ) is an experienced Translator who has been actively engaging in translation since the 1980s. She plays an important role in the Singapore translation scene and is a versatile translator. Goh first started her career in The Straits Times Bilingual Edition as a Reporter. This brought her into the world of translation which saw her engaging in Literary, Arts and Culture translation and criticism. Goh’s foray into literary translation have seen her translate the literary works of Cultural Medallion recipient Yeng Pway Ngon. However, she is not just any literary translator of Yeng’s, but also his lifelong companion, supporting his literary career through her translations. Her literary translations first introduced Yeng’s works to English readers in and outside of Singapore. While Goh is a pioneering individual in the Literary translation scene and an accomplished translator in her own right, there is currently very few research in academia summarizing her contributions as a translator in Singapore. In fact, literature on the translation scene in Singapore in the 1980s is sparse. It was also noted that the practice of translation in the 1980s was almost a male exclusive one. Not only does this bring to the foreground the problem of the Translator’s Invisibility, we see that Gender Awareness has been unfairly skewed such that the Female Translator has become invisible. The Female Translator has also been relegated to the bottom of the social ladder due to culture and power differences. Using Gender and Translation as a theoretical framework, this paper attempts to study the contributions of Goh Beng Choo in translation, and would show how Goh displays her voice and cultural identity as a female translator in a male dominant society. In her seminal work involving Gender and Translation, Sherry Simon sees translation as “a strong form of expression for women”. Simon’s work also unearths “the neglected intellectual and literary work of women”, presenting a multitude of voices in translation. This paper would portray how Goh as a protector of Arts and Culture, raises awareness and cultivates an appreciation of the Arts through her translations. We would also show that in displaying the Translator’s Subjectivity in her Literary Translations, Goh attempts to subvert the dominant male discourse present in society, resulting in the betterment of the position of the female in society, at the same time advocating for better recognition for both female translators and the practice of translation in the industry.